A Novel Update on the Management of Mller-Weiss Disease: Presentation of a Treatment Algorithm - Chayanin Angthong; Alastair S.E. Younger; Bavornrit Chuckpaiwong; Thos Harnroongroj; Andrea Veljkovic (My University, 2023)
Objective Müller-Weiss disease (MWD) is a challenging condition involving the perinavicular region in the initial stages and subsequently the entire foot in the later stages. The goal of this article is to describe the pathomechanics, clinical evaluation, and nonoperative and operative treatment, including a treatment algorithm, based on current evidence and the combined authors’ experience. Design We review the related articles and summarize the information about this condition. Results A number of related articles reveal that the treatments should focus on the management of degenerative regions and deformity correction to restore normal foot alignment and provide pain relief. Conclusion This systematic review proposes a treatment algorithm that is comprehensive and practical to apply for the management of MWD.
Keywords: Presentation (obstetrics); Foot and Ankle Surgery